Enhancing luminescence properties of lanthanide(iii)/pyrimidine-4, 6-dicarboxylato system by solvent-free approach1. Issue 15 (21st April 2015) - Cepeda, Javier; Pérez-Yáñez, Sonia; Beobide, Garikoitz; Castillo, Oscar; García, José Ángel; Lanchas, Mónica; Luque, Antonio
<x xml:space="preserve">Abstract</x> Solvent-free reaction between lanthanide nitrates and pyrimidine-4, 6-dicarboxylic acid led to 3D frameworks with coordinated nitrates showing a photoluminescence improvement and waveguiding behaviour.